Sexual adjustment and body image of mastectomized women due to breast cancer - Blanco Picabia, Alfonso; Vázquez-Ortiz, Jerónima; Antequera, Rosario (Psicooncología, 2010)
The aim of the present study is to analyze the effects that a mastectomy, due to breast cancer, has on the psychosexual adjustment and body image of women. On the one hand, sixty mastectomized women were assessed (thirty of them had been operated on less than one year ago, and the other thirty women had been operated on more than one year ago); on the other hand, thirty healthy women were assessed as a control group. The following measuring instruments were used: The Sexual Arousal and Satisfaction Scales of S.A.I.-Expanded, the Subscale of Physical Self-concept of the Selfconcept Scale of Tennessee and a structured interview created by us. In the results we did not find any statistically significant differences among the groups as regards sexual arousal and satisfaction, nor in the frequency of sexual encounters or orgasms, or in physical selfconcept. Nevertheless, about fifty per cent of women expressed that after the mastectomy they were worried about the resumption of their sexual encounters, they were afraid of being rejected by their partners and they had noticed a decrease in sexual interest. Likewise there is a significantly greater major number in both groups of mastectomized women who do not receive any caresses from their partners in the area of their breasts, who have more problems related to their own nakedness, and have a more negative assessment of their physical attractiveness. We concluded that the mastectomized women have alterations in sexuality and body image that remain after the first year after mastectomy, when there is no psychological intervention.
Keywords: Breast cancer; Mastectomy; Body image; Sexuality